The Flourishing Language Learner: A Systematic Review of Positive Psychology and Motivation in English Language Learning - Sahril Nur; Auliyanti Sahril Nurfadhilah (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
The field of second language acquisition has witnessed a "positive turn," shifting focus from learner deficits to the factors that enable learners to thrive. This systematic review synthesizes and critically examines the nexus of positive psychology (PP) and motivation within diverse English language learning contexts—English as a Foreign Language (EFL), English as a Second Language (ESL), and native speaker (L1) literacy—from 2015 to 2024. Following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we conducted a comprehensive search of major academic databases (Scopus, Web of Science, ERIC, PsycINFO), yielding 68 empirical studies that met our inclusion criteria. Thematic analysis of these studies revealed several key findings. First, research is dominated by a few cores PP constructs, namely grit, growth mindset, foreign language enjoyment (FLE), and resilience, with learner well-being emerging as a holistic and integrative concept. Second, these PP constructs demonstrate a strong, positive mediational or predictive relationship with key motivational frameworks, particularly Dörnyei's L2 Motivational Self System. Third, significant contextual disparities exist: the bulk of research is situated in EFL contexts, focusing on classroom-based emotions and academic achievement; ESL research highlights resilience and socio-cultural adaptation; and the L1 context remains critically under-explored, with a focus on academic mindset rather than language-specific motivation. Finally, a growing number of studies propose and test PP-informed pedagogical interventions, such as gratitude journaling and strengths-based feedback, demonstrating promising but nascent evidence of their efficacy. This review consolidates a decade of research, highlighting the crucial role of positive psychological attributes in sustaining motivation for language learning. It concludes by outlining critical gaps in the literature and proposing a research agenda that calls for more longitudinal, interventionist, and contextually diverse studies to build a more comprehensive understanding of how to foster flourishing English language learners.